Liquid‐Mediated Three‐Dimensional Scanning Probe Nanosculpting. Issue 17 (2nd April 2013) - Gan, Tiansheng; Zhou, Xuechang; Ma, Chunfeng; Liu, Xuqing; Xie, Zhuang; Zhang, Guangzhao; Zheng, Zijian
<x xml:space="preserve">Abstract</x> 3D functional polymer brushes are fabricated by liquid‐mediated scanning probe nanosculpting (LSPN). Surface‐tethered functional polymer brushes, which are immersed in their good solvent, are mechanically cleaved away from the substrate by the AFM tip at high forces, and immediately imaged in situ with the same AFM tip at low applied forces. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>